Non-Trileaflet Aortic Valve Aortopathies - Abdelrahman Ahmed; Tom Kai Ming Wang (Life)
The incidence of thoracic aortic aneurysms (TAAs) is approximately 10.4 cases per 100,000 person-years. Although most cases of TAA are caused by degenerative disease, associated aortic valve abnormalities have been heavily linked to this condition. These include unicuspid, bicuspid and quadricuspid aortic valves. These non-tricuspid aortic valves occur sporadically but can occur in familial clusters with variable penetrance. The presence of non-tricuspid aortic valves has significant implications for patients, as they become prone to valvular dysfunction and aortic dissection. Therefore, understanding of the pathophysiology and natural history of this condition is imperative for early diagnosis, regular surveillance and timely intervention. In this review article, we discuss the normal anatomy of the aortic valve, non-tricuspid aortic valves and their association with TAAs. We also highlight the role of various cardiac imaging modalities in the management of affected patients.